The Fluid-structure Coupling Analysis of Steel-Wire-Reinforced Flexible Pipe Under Inner Fluid Pressure Impact - Shouyuan, Zhang (European Journal of Computational Mechanics, 2021)
Identifying dynamic characteristics of the fluid filled steel-wire-reinforced flexible pipe is vital in controlling the pipe vibration. A direct fluid-structure coupling method based on finite element analysis is proposed and validated by modal simulation of an oil filled T-shape pipe. An innovative way of modeling steel-wire-reinforced rubber pipe is put forward. The modeling method is validated by modal test of the water-filled pipe. The 2nd Mooney-Rivlin constitutive model is used for the rubber material. Transient dynamic simulations of a bending steel-wire-reinforced pipe filled with water under step and sine-shape pressure impact are performed for the first time. Different fluid turbulence models are used to evaluate the influences on pipe vibration. The dynamic characteristics of the water filled flexible pipe is researched under different fluid pressures. The vibration peak frequencies of the water-filled pipe under various impact excitations coincide well with the fluid-structure coupling modes of the pipe.